The Effect of Entrepreneurial Education on Entrepreneurial Intention Through Individual Entrepreneurial Orientation in Double Track Program Students at Mojokerto Private High School - Wati, Indah Kumoro; Fulgentius Danardana Murwani; Eka Ananta Sidharta (International Journal of Technology and Education Research, 2025)
As one of the most influential factors, entrepreneurial intention can determine whether individuals will take concrete steps toward the business world or not. This study aims to determine the direct and indirect effects of entrepreneurial education on entrepreneurial intention through individual entrepreneurial orientation. The research method used is quantitative with a cross-sectional design. The research sample consists of 253 respondents from Al-Hidayah High School and Tamansiswa High School in Mojokerto City. The results show that entrepreneurial education has an effect on proactivity. Entrepreneurial education influences risk-taking. Entrepreneurial education influences innovation. Proactivity influences entrepreneurial intention. Risk-taking does not influence entrepreneurial intention. Innovation influences entrepreneurial intention. Proactivity has a mediating effect on entrepreneurial education on entrepreneurial intention. Risk-taking does not have a mediating effect on entrepreneurial education on entrepreneurial intention. Innovation does not have a mediating effect on entrepreneurial education on entrepreneurial intention